The Oxford Handbook of the Books of Kings - McKenzie, Steven L. (Oxford Handbooks Series, 2024)
"A premier reference work for the study of the Books of Kings, this volume will provide a clear and useful introduction to the main aspects and issues pertaining to the scholarly study of Kings. These include: textual history (including the linguistic profile), compositional history, literary approaches, key characters, history, important recurring themes, reception history and some contemporary readings. As a one-volume introduction embracing all the aspects of the study of Kings, written by an international and diverse team of scholars, this handbook is the ideal point of entry into the study of Kings for generations of students and scholars"--